2018
DOI: 10.1002/acr.23272
|View full text |Cite
|
Sign up to set email alerts
|

Education Preferences of People With Gout: Exploring Differences Between Indigenous and Nonindigenous Peoples from Rural and Urban Locations

Abstract: Māori and NZEuropean individuals with gout report different understandings and education preferences around personal triggers of gout, treatment options, and ways of receiving information about gout. Further research is required to develop ethnicity-specific gout education resources internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…18 Findings from this overall study previously revealed commonalities in Māori and Pākehā gout patients' desire for information about diet and medication, but also showed differences in preferred communication channels, with Māori being less likely to prioritise information about gout from a doctor and preferring spoken over written information about gout. 19 In our previous paper, we documented quantitative ranking data on gout educational preferences made during a focus group ranking exercise. 19 The present paper describes data from the discussions arising during the focus group study reported in the previous paper.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Findings from this overall study previously revealed commonalities in Māori and Pākehā gout patients' desire for information about diet and medication, but also showed differences in preferred communication channels, with Māori being less likely to prioritise information about gout from a doctor and preferring spoken over written information about gout. 19 In our previous paper, we documented quantitative ranking data on gout educational preferences made during a focus group ranking exercise. 19 The present paper describes data from the discussions arising during the focus group study reported in the previous paper.…”
Section: Introductionmentioning
confidence: 99%
“…19 In our previous paper, we documented quantitative ranking data on gout educational preferences made during a focus group ranking exercise. 19 The present paper describes data from the discussions arising during the focus group study reported in the previous paper. 19 The aim of the present analysis was to explore experiences of gout education in primary health care from the perspectives of Māori and Pākehā people with gout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the degree of education was not significantly associated with gout development, patients with tertiary level of education displayed a lower tendency to develop gout (OR = 0.32). Possibly, individuals with a lower level of education are less aware of risk factors for diseases and have a poorer understanding about the importance of preventive measures against gout (Treharne et al, 2018). Education preferences in gout patients were identified in some New Zealand populations (Treharne et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, individuals with a lower level of education are less aware of risk factors for diseases and have a poorer understanding about the importance of preventive measures against gout (Treharne et al, 2018). Education preferences in gout patients were identified in some New Zealand populations (Treharne et al, 2018). In the literature, a well-known co-factor of gout is alcohol usage (Lieber, 1965;Teng et al, 2013;Seki et al, 2016), corresponding to increased serum uric acid concentration.…”
Section: Discussionmentioning
confidence: 99%